Genetic variability for seed yield and its related traits in M3 mutants of green gram (Vigna radiata (L.) Wilczek) - Mohammad Rafiq Wani (Journal of Tropical Agriculture, 2025)
Mutation breeding is an auxiliary approach to traditional breeding, enhancing genetic diversity and providing essential raw materials for developing high-quality plants through selective breeding techniques. This research was aimed at evaluating the extent of induced genetic variability for various yield-related traits in M3 mutants of green gram variety PDM-11 after treatments with 0.2% and 0.03% of ethyl methanesulfonate (EMS) and hydrazine hydrate (HZ). Three replications of 100 seeds each were sown for every treatment and control in randomized complete block design (RCBD). Significant increase in mean values for fertile branches per plant, pods per plant, seeds per pod and total seed yield (g) was noticed among the M3 mutants. EMS treatments were more effective in increasing the mean values for all the yield attributing traits than HZ treatments. The mutant PDM-11A demonstrated the highest increase of 83.7% in seed yield over the control. Compared to the control, analysis of variance revealed increased genetic parameters viz., genotypic coefficient of variation (GCV), heritability (H2) and genetic advance (GA) for seed yield and yield components in the mutants. The rise in mean values, coupled with improved genetic variability for traits associated with seed yield, indicates the potential for identifying more favorable lines with improved yield capacity. Furthermore, a positive phenotypic correlation was noted between the yield components. On the other hand, the protein content of the mutant seeds showed an inverse relationship with total plant yield, indicating that different genetic processes regulate these two traits. These findings highlight the potential of induced mutagenesis, particularly EMS treatments, in enhancing yield-related traits in green gram. The observed genetic variability and improved agronomic performance of the mutants suggest their suitability for further breeding programs aimed at developing high-yielding green gram varieties.